Arthroscopy-Assisted Reconstruction of the Coracoclavicular and Acromioclavicular Ligaments Using a Tendon Graft and Knot-Hiding Clavicular Implants in Chronic Acromioclavicular Separations - Ranne Juha O; Salonen Severi O; Lehtinen Janne T (ELSEVIER, 2025)
The purpose of this study is to introduce an arthroscopy-assisted technique to treat chronic acromioclavicular (AC) dislocation. The method involves reconstructing both the coracoclavicular (CC) and AC ligaments in a practical and reliable way using a semi-tendon graft and knot-hiding implants. In the CC reconstruction, the anterior graft limb re -places the trapezoid ligament, whereas the dorsal limb is wrapped around the dorsal edge of the clavicle to reconstruct the conoid ligament. One 5.5-mm drill hole is needed in the clavicle since the semitendinosus graft and the inter-connecting supportive suture share the same drill hole. A 2.4-mm drill hole through the coracoid is needed for the interconnective suture. The technique uses knot-hiding titanium implants that are designed to be used with a tendon graft. After finishing the arthroscopic CC reconstruction, the dorsal end of the tendon graft is openly taken over the AC joint to openly reconstruct the superior AC ligament. The AC capsule is then plicated over the reconstruction. The arthroscopic part of the reconstruction is not technically difficult for an experienced arthroscopic shoulder surgeon. For success, it is essential to achieve a tension-free reduction of the distal clavicle and to provide sufficient recovery time postoperatively.